CRITERIA AND METHODS FOR OPTIMIZING PRODUCTION PROJECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis discusses the issues of optimizing technological processes in enterprises, their impact on efficiency, and advanced optimization methods. It is substantiated that optimization makes it possible to increase production volumes, use resources efficiently, and reduce production costs. The optimization of technological processes in enterprises plays an important role in increasing the efficiency of modern production systems. This process enables growth in production output, conservation of resources, reduction of energy consumption, and improvement of product quality.